Appreciative leadership: delivering sustainable difference through conversation and inquiry. Issue 1 (28th January 2014) - MacNeill, Fiona; Vanzetta, Jillian
Abstract : Purpose: – This paper reflects a two-year evaluation research study by Fiona MacNeill Associates (FMA), focused on an Appreciative Leadership Programme. The aim of this study was to explore the impact of designing a bespoke Appreciative Leadership Programme (commissioned by Lancashire Care NHS Foundation Trust), around a specific set of organisational values and the associated sustainability linked to the delivery using conversation and inquiry. Design/methodology/approach: – The paper is a review of 497 delegates and their associated 423 line managers. The main evaluation methods were questionnaires, conversations, content analysis and thematic analysis. The research collects data pre, during, end and post-programme. Findings: – The analysis of data collected indicates a statistically significant link between the programme design and delivery and the subsequent sustainability of the learning and levels of engagement within the organisation. Research limitations/implications: – The research provided information on all key areas of inquiry and allowed improvements to be made for future programmes. In future study, a focused follow up with a larger sample of at least 30 per cent of the total population will provide greater validity and reliability of the impact of on-going positive attention. The evaluation of leadership learning sets also needs to be more focused. Practical implications: – The findings can be used to inform the next iteration of the programme, by building on areas of strength and those identified for development. The data allows the organisation (LCFT) and the provider to co-create the next programme. The findings have also been presented to other NHS organisations and to an international training and development conference in Dallas. Originality/value: – Appreciative Leadership is built on the foundation of Appreciative Inquiry (AI), whole systems thinking, and action research. The organisation is seen as a relationship to be explored and developed, teams as communities of purpose and practice, and individuals as thinkers and innovators. This approach favours interdependencies, conversation, novel and creative ideas, and engagement that fosters a true desire to co-create the future. The paper provides connections between concepts and theories used in the education of clinicians and cutting-edge leadership development thinking. The paper has value to leaders, and those who commission leadership development, healthcare professionals and training and development professionals.